Landscape genetics of a threatened maple, Acer miyabei: Implications for restoring riparian forest connectivity - Saeki, Ikuyo; Hirao, Akira S.; Kenta, Tanaka; Nagamitsu, Teruyoshi; Hiura, Tsutom (Biological Conservation, 2018)
Because forest fragmentation affects ecological connectivity, establishing corridors is increasingly important in conserving biodiversity. Conserving the connectivity of riparian forests should be a priority because they often support rich and unique biota but are greatly modified by humans. Acer miyabei is a threatened maple which grows in floodplain ecosystems in northern Japan. We examined the effects of forest fragmentation on its genetic connectivity and identified candidate areas to be restored as riparian forest corridors. We collected leaf samples from 290 of A. miyabei individuals in 13 populations and determined pairwise genetic distances among the populations using 12 microsatellite loci. We also calculated geographic and resistance distances; the latter was quantified by least-cost path and circuit theory models by designating forested or riparian forested areas as having lower resistance than other types of land use. According to multiple regression analyses, genetic distance showed significant positive relationships with resistance distance but was not significantly related to geographic distance. The results indicate that forest fragmentation impedes gene flow of the species. Genetic differentiation among populations was greater in the smaller tree group than in larger one, suggesting that more recently established individuals are exposed to greater genetic isolation than the mature individuals owing to increasing forest fragmentation over time. Reduction of genetic connectivity was conspicuous in and around deforested areas. Such areas can be targeted for promoting connectivity of riparian habitats in future landscape planning.